The emotionally intelligent team : - Hughes, Marcia M. (Jossey-Bass, 2007)
The Emotionally Intelligent Team connects the dots between the task at hand, achieving and making a difference, and personal happiness. Imagine where humankind would be if every entity on the planet operated within a series of high performing teams.